RIM-ONE: An open retinal image database for optic nerve evaluation - Fumero, F.; Alayon, S.; Sanchez, J. L.; Sigut, J.; Gonzalez-Hernandez, M. (2011 24th International Symposium on Computer-Based Medical Systems (CBMS), 2011)
Automated diagnosis of glaucoma disease has been studied for years. A great amount of research work in this field has been focused on the analysis of retinal fundus images to localize, detect and evaluate the optic disc. An open fundus image database with accurate gold standards of the optic nerve head has been implemented. A variability measurement by zones of the optic disc is also proposed. The relevance of this work is to provide accurate ONH segmentations and a segmentation assessment procedure to allow the design of computerized methods for glaucoma detection.